Molybdenum ore tailing ceramsite preparation device and method
By introducing support blocks, fixing rods, preparation body and adjustment mechanism into the ceramic processing equipment, the problem of low collection efficiency caused by the need for height adjustment of existing equipment is solved, and the efficiency improvement and operation convenience of the ceramic processing process are achieved.
Patent Information
- Application Number
- CN202411388227.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-05
- Publication Date
- 2025-01-07
AI Technical Summary
The existing ceramic pellet processing equipment requires height adjustment, resulting in low collection efficiency during processing.
A molybdenum tailings ceramic preparation device is designed, including a support block, a fixing rod, a preparation body, a connecting block and an adjustment mechanism, by placing blocks, motors, rotating columns, gears, fixing blocks, through holes, adjustment columns and cards The combination of grooves achieves precise adjustment of the height of the preparation body and simplifies the collection process of the finished product.
It improves the efficiency of the ceramic processing process, facilitates the collection and processing of finished products, and ensures the stability and operation convenience of the equipment.
Smart Images

Figure CN119260881A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field related to ceramsite, and in particular to a device and method for preparing molybdenum ore tailings ceramsite. Background Art
[0002] Clay ore, as the name suggests, is ceramic particles. Most of the appearance characteristics of clay ore are round or oval spheres, but some imitation gravel clay ore are not round or oval spheres, but irregular gravel. The shape of clay ore varies due to different processes. Its surface is a hard shell, which is ceramic or glazed, has the function of water insulation and air retention, and gives clay ore higher strength. Because there are many raw materials for producing clay ore, there are many varieties of clay ore, so there are many colors. The color of roasted clay ore is mostly dark red and ochre red. There are also some special varieties of gray-yellow, gray-black, gray-white, blue-gray, etc. The color of unfired clay ore varies due to the different solid waste used. It is generally gray-black, and the surface has no glossiness, which is not as smooth as roasted clay ore. The particle size of clay ore is generally five to twenty mm, and the maximum particle size is twenty-five mm. Clay ore is generally used to replace gravel and pebbles in concrete. Lightweight is the main feature of clay ore. The most important point among the excellent properties is also the main reason why it can replace heavy sand and gravel. The internal structure of ceramsite is characterized by fine honeycomb micropores. These micropores are closed rather than connected. They are formed by the gas being wrapped in the shell. This is the main reason why ceramsite is light. The fine particle part of ceramsite is called ceramsite sand. There are many fine particles less than five millimeters in ceramsite. In production, this part of fine particles is screened out by a screening machine, which is customarily called ceramsite sand. The density of ceramsite sand is slightly higher, and the chemical and thermal stability are good. Ceramsite sand is mainly used to replace natural river sand or mountain sand to prepare lightweight aggregate concrete and lightweight mortar. It can also be used as fine aggregate for acid-resistant and heat-resistant concrete. The main varieties include clay ceramsite sand, shale ceramsite sand and fly ash ceramsite sand. The purpose of using ceramsite sand is also to reduce the dead weight of the building. Ceramsite sand can also be used for soilless cultivation and industrial filtration. Therefore, a molybdenum ore tailings ceramsite preparation device and method are particularly needed.
[0003] However, the existing testing devices need to be processed during the testing process. During the processing, the equipment for preparing expanded clay needs to be highly adjusted. Most expanded clay processing equipment may be difficult to collect after processing due to different angles, which reduces the work efficiency to a certain extent. Summary of the invention
[0004] The object of the present invention is to provide a device and method for preparing molybdenum ore tailings ceramsite, so as to solve the problem that the existing testing device proposed in the above background technology needs to be processed during the test, and the equipment for preparing ceramsite needs to be highly adjusted during the processing. Most of the ceramsite processing equipment may be difficult to collect after processing due to different angles, thus reducing the work efficiency to a certain extent.
[0005] To achieve the above object, the present invention provides the following technical solutions: a molybdenum tailings ceramsite preparation device and method, comprising a support block, the upper surface of the support block is fixedly connected to a fixing rod, a side surface of the fixing rod is fixedly connected to a preparation body, the lower surface of the preparation body is fixedly connected to a connecting block, and the lower surface of the connecting block is provided with an adjustment mechanism;
[0006] The adjustment mechanism includes a placement block, a motor, a rotating column, a gear, a fixed block, a through hole, an adjustment column and a slot. The placement block is placed on one side surface of the support block, the motor is installed on the inner surface of the placement block, the rotating column is fixedly connected to one side surface of the motor, the gear is fixedly connected to one side surface of the rotating column, the fixed block is placed on one side surface of the placement block, a through hole is provided on one side surface of the fixed block, the adjustment column is installed on the inner surface of the through hole, and a slot is provided on the outer surface of the adjustment column.
[0007] Preferably, the fixing rods are symmetrically installed with respect to the length center axis of the support block, and the connecting blocks are symmetrically installed with respect to the width center axis of the preparation body.
[0008] Preferably, the outer surface size of the motor matches the inner surface size of the placement block, and the motor forms a threaded structure through a rotating column and a gear.
[0009] Preferably, the outer surface size of the rotating column matches the inner surface size of the through hole, and the outer surface size of the adjusting column matches the inner surface size of the fixing block.
[0010] Preferably, the slots are provided at equal intervals on the outer surface of the adjusting column, and the gears are meshedly connected with the slots.
[0011] Preferably, the placement block is installed symmetrically with respect to the length center axis of the support block, and the fixing block is installed symmetrically with respect to the length center axis of the support block.
[0012] Preferably, it is characterized by the following steps:
[0013] The preparation method of molybdenum tailings ceramsite mainly includes the following steps:
[0014] S1. Raw material preparation;
[0015] S2, mixing and granulation;
[0016] S3. Maintenance.
[0017] Preferably, it is characterized by the following steps:
[0018] Preparation process of ceramsite:
[0019] S1. Preparation of raw materials;
[0020] S2, drying and preheating;
[0021] S3, sintering;
[0022] S4. Special treatment.
[0023] Preferably, the special treatment in S4 includes sludge treatment, hardener premixing, granulation, hardening reaction and curing treatment.
[0024] Compared with the prior art, the invention has the following beneficial effects: the molybdenum ore tailings ceramsite preparation device and method:
[0025] 1. The motor is placed in the placement block through the arrangement of a placement block, a motor, a rotating column, a gear, a fixed block, a through hole, an adjusting column and a slot. Then the motor is started to drive the rotating column. The rotating column penetrates the through hole to drive the gear to rotate. The gear drives the slot on the outside of the adjusting column to engage and connect. Thus, the adjusting column is adjusted to adjust the height of the preparation body, thereby facilitating the collection of the prepared finished products.
[0026] 2. In the preparation method of molybdenum tailings ceramsite, raw materials are prepared, wherein the raw materials include molybdenum tailings, ceramic polishing waste powder, fly ash, limestone powder, cement, gypsum, alkali activator and water, wherein the 45μm sieve residue of fly ash should be ≤20wt%, the ignition loss is 5-10wt%, the SO3 content is 0.5-3wt%, and the calcium oxide content is 1-5wt%; the 45μm sieve residue of limestone powder should be ≤10wt%; the grade of cement is not less than 42.5; the ingredients of the alkali activator include 15-25wt% of sodium sulfate, 30-50wt% of calcium oxide, 3-7wt% of gypsum, 15-25wt% of sodium silicate, and 1-5wt% of sodium hydroxide. 0~20wt%, in addition, the raw material components also include grinding aids. After the prepared raw materials are processed and mixed, granulation treatment is carried out to obtain a mixture. This step may include mixing and grinding an alkali activator and gypsum in the presence of a grinding aid to obtain a prefabricated material; then the prefabricated material is mixed with molybdenum tailings, ceramic polishing waste powder, fly ash, limestone powder, cement and water to obtain a mixture; the mixture is granulated and then cured to obtain molybdenum tailings ceramsite. The granulated ceramsite needs to be cured to ensure that it has good impermeability and compression resistance, as well as good later strength. The curing conditions may include the control of temperature, humidity and time to ensure the quality of the ceramsite.
[0027] 3. In the preparation process of molybdenum tailings ceramsite, the curing stage is a crucial step. The precise control of curing conditions has a decisive influence on the final performance of ceramsite. Normally, the curing temperature should be controlled between 20℃ and 80℃ to ensure that the chemical reaction inside the ceramsite can proceed smoothly, and the humidity should be maintained in the range of 60% to 90% relative humidity to prevent the surface of the ceramsite from losing water too quickly and causing cracks. The curing time is generally 24 to 72 hours, and the specific time depends on the expected performance requirements of the ceramsite. During the curing process, the chemical reaction inside the ceramsite mainly includes the reaction of the alkali activator with the active ingredients in the raw materials such as fly ash and limestone powder to generate hydration products such as hydrated calcium silicate and hydrated calcium aluminate. These hydration products It can fill the pores inside the ceramsite and improve its density and strength. At the same time, gypsum plays a role in regulating the hydration rate during the curing process to ensure that the hydration reaction inside the ceramsite is carried out evenly. After the curing is completed, the ceramsite needs to be dried to remove excess water. The drying temperature is generally controlled between 60°C and 100°C, and the drying time is about 12 to 24 hours. The dried ceramsite should be screened to remove unqualified particles and ensure that the particle size distribution of the ceramsite meets the use requirements. The final molybdenum tailings ceramsite has good physical and chemical properties and can be widely used in the construction field, such as lightweight aggregate, thermal insulation material, sound-absorbing material, etc. In addition, since its raw materials contain a large amount of industrial waste, such as molybdenum tailings and fly ash, the preparation process of the ceramsite also has the significance of environmental protection and resource recycling. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the overall appearance structure of the device of the present invention;
[0029] Figure 2 This is a schematic diagram of the structure of the motor and the rotating column of the present invention working together;
[0030] Figure 3 For the present invention Figure 2 A schematic diagram of the enlarged structure at point A;
[0031] Figure 4 The present invention is a schematic structural diagram of a method for preparing molybdenum tailings ceramsite;
[0032] Figure 5 It is a schematic diagram of the structure of the ceramsite process of the present invention.
[0033] In the figure: 1. support block; 2. fixing rod; 3. preparation main body; 4. connection block; 5. adjustment mechanism; 501. placement block; 502. motor; 503. rotating column; 504. gear; 505. fixing block; 506. through hole; 507. adjustment column; 508. slot. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] See also Figure 1-5 The present invention provides a technical solution: a molybdenum tailings ceramsite preparation device and method, comprising a support block 1, a fixing rod 2 is fixedly connected to the upper surface of the support block 1, a preparation body 3 is fixedly connected to one side surface of the fixing rod 2, a connection block 4 is fixedly connected to the lower surface of the preparation body 3, and an adjustment mechanism 5 is arranged on the lower surface of the connection block 4;
[0036] The adjustment mechanism 5 includes a placement block 501, a motor 502, a rotating column 503, a gear 504, a fixed block 505, a through hole 506, an adjustment column 507 and a slot 508. The placement block 501 is placed on one side surface of the support block 1, the motor 502 is installed on the inner side surface of the placement block 501, the rotating column 503 is fixedly connected to one side surface of the motor 502, the gear 504 is fixedly connected to one side surface of the rotating column 503, the fixing block 505 is placed on one side surface of the placement block 501, the through hole 506 is opened on one side surface of the fixing block 505, and the adjustment column 507 is installed on the inner side surface of the through hole 506 A slot 508 is provided on the outer surface of the adjusting column 507. By configuring a placement block 501, a motor 502, a rotating column 503, a gear 504, a fixing block 505, a through hole 506, an adjusting column 507 and a slot 508, the motor 502 is placed in the placement block 501. Then, the motor 502 is started to drive the rotating column 503. The rotating column 503 penetrates the through hole 506 to drive the gear 504 to rotate. The gear 504 drives the slot 508 on the outer side of the adjusting column 507 to engage with the adjusting column 507, thereby adjusting the height of the preparation body 3.
[0037] Furthermore, the fixing rod 2 is symmetrically installed with respect to the length center axis of the supporting block 1, and the connecting block 4 is symmetrically installed with respect to the width center axis of the preparation body 3. By setting the fixing rod 2, the stability and bearing capacity of the entire structure are ensured.
[0038] Furthermore, the outer surface size of the motor 502 matches the inner surface size of the placement block 501, and the motor 502 forms a threaded structure with the rotating column 503 and the gear 504. Through the setting of the motor 502, precise rotational motion can be achieved, thereby driving the operation of the entire device.
[0039] Furthermore, the outer surface size of the rotating column 503 matches the inner surface size of the through hole 506, and the outer surface size of the adjusting column 507 matches the inner surface size of the fixing block 505. Through the setting of the rotating column 503, the user can easily complete the installation and adjustment of the equipment through simple rotation and adjustment actions.
[0040] Furthermore, the slots 508 are provided at equal intervals on the outer surface of the adjustment column 507, and the gears 504 are meshedly connected with the slots 508. Through the arrangement of the gears 504, the adjustment column 507 can realize adjustment movement, thereby enhancing the convenience of its operation.
[0041] Furthermore, the placement block 501 is symmetrically installed with respect to the length center axis of the support block 1, and the fixing block 505 is symmetrically installed with respect to the length center axis of the support block 1. By setting the placement block 501, the stability and balance of the entire structure are ensured, thereby further enhancing the reliability of the system.
[0042] Further, it is characterized by the following steps:
[0043] The preparation method of molybdenum tailings ceramsite mainly includes the following steps:
[0044] S1. Raw material preparation;
[0045] S2, mixing and granulation;
[0046] S3. Maintenance.
[0047] Further, it is characterized by the following steps:
[0048] Preparation process of ceramsite:
[0049] S1. Preparation of raw materials;
[0050] S2, drying and preheating;
[0051] S3, sintering;
[0052] S4. Special treatment.
[0053] Furthermore, the special treatment in S4 includes sludge treatment, hardener premixing, granulation, hardening reaction and curing treatment.
[0054] In the preparation method of molybdenum tailings ceramsite, raw materials are prepared, wherein the raw materials include molybdenum tailings, ceramic polishing waste powder, fly ash, limestone powder, cement, gypsum, alkali activator and water, wherein the 45μm sieve residue of the fly ash should be ≤20wt%, the ignition loss is 5-10wt%, the SO3 content is 0.5-3wt%, and the calcium oxide content is 1-5wt%; the 45μm sieve residue of the limestone powder should be ≤10wt%; the grade of cement is not less than 42.5; the components of the alkali activator include 15-25wt% of sodium sulfate, 30-50wt% of calcium oxide, 3-7wt% of gypsum, 15-25wt% of sodium silicate, 10 ~20wt%, in addition, the raw material components also include a grinding aid. After the prepared raw materials are processed and mixed, granulation treatment is carried out to obtain a mixture. This step may include mixing and grinding an alkali activator and gypsum in the presence of a grinding aid to obtain a prefabricated material; then the prefabricated material is mixed with molybdenum tailings, ceramic polishing waste powder, fly ash, limestone powder, cement and water to obtain a mixture; the mixture is granulated and then cured to obtain molybdenum tailings ceramsite. The granulated ceramsite needs to be cured to ensure that it has good impermeability and compression resistance, as well as good later strength. The curing conditions may include temperature, humidity and time control to ensure the quality of the ceramsite.
[0055] In the preparation process of molybdenum tailings ceramsite, the curing stage is a crucial step. The precise control of curing conditions has a decisive influence on the final performance of ceramsite. Normally, the curing temperature should be controlled between 20℃ and 80℃ to ensure that the chemical reaction inside the ceramsite can proceed smoothly, and the humidity should be maintained in the range of 60% to 90% relative humidity to prevent the surface of the ceramsite from losing water too quickly and causing cracks. The curing time is generally 24 to 72 hours, and the specific time depends on the expected performance requirements of the ceramsite. During the curing process, the chemical reaction inside the ceramsite mainly includes the reaction of the alkali activator with the active ingredients in the raw materials such as fly ash and limestone powder to generate hydration products such as hydrated calcium silicate and hydrated calcium aluminate. These hydration products can fill the pores inside the ceramsite and improve its density and strength. At the same time, gypsum plays a role in regulating the hydration rate during the curing process to ensure the performance of the ceramsite. The hydration reaction inside the particles is carried out evenly. After curing, the expanded clay needs to be dried to remove excess moisture. The drying temperature is generally controlled between 60°C and 100°C, and the drying time is about 12 to 24 hours. The dried expanded clay should be sieved to remove unqualified particles and ensure that the particle size distribution of the expanded clay meets the use requirements. The final molybdenum tailings expanded clay has good physical and chemical properties and can be widely used in the construction field, such as as lightweight aggregate, thermal insulation material, sound-absorbing material, etc. At the same time, the ratio and pretreatment of raw materials are also crucial. Reasonable raw material ratio can ensure that the expanded clay obtains the best performance in subsequent chemical reactions. Usually, the mixing ratio of molybdenum tailings, fly ash and limestone powder needs to be optimized according to experimental data to achieve the expected strength and density requirements. The pretreatment step includes fine grinding of the raw materials to increase their reactivity and remove harmful substances such as heavy metals. During the production process, attention should also be paid to the influence of environmental factors. Since a certain amount of dust and exhaust gas will be generated during the production of ceramsite, corresponding environmental protection facilities such as bag filters and desulfurization devices are required to reduce pollution to the environment. In addition, the wastewater generated during the production process also needs to be treated to meet the emission standards. The production of molybdenum tailings ceramsite is not only environmentally friendly, but also can provide a sustainable alternative to traditional building materials. With the increasing demand for environmentally friendly materials in the construction industry, the application prospects of molybdenum tailings ceramsite are very broad. In addition to its application in the construction field, molybdenum tailings ceramsite can also be used in fields such as soil improvement, water treatment and landscaping, providing new ideas for environmental protection and resource recycling, and demonstrating its excellent performance through demonstration projects, thereby promoting its wide application in the market. At the same time, the government and industry associations should also introduce corresponding policies and standards to encourage and regulate the production and application of molybdenum tailings ceramsite to promote its healthy and orderly development.
[0056] In the preparation process of ceramsite, the raw materials are first crushed and screened, and then made into raw materials of different particle sizes by rolling, balling and other methods, followed by drying and preheating. The temperature of the raw materials is controlled between 400℃ and 600℃ in the preheating stage. In the preheating stage, the organic matter and carbonate in the raw materials begin to decompose and volatilize to produce gas, and then sintering is carried out to solid-solution bond the prepared green particles at high temperature without expansion. The sintering method mainly uses a sintering machine, which is suitable for sintering materials with stationary green particles. In the preparation of special ceramsite, such as sewage, For mud ceramsite, sludge treatment is carried out on it, the river silt is deeply dehydrated, and then the mud cake is crushed to ensure that the silt is suitable for subsequent processes, and then the hardener is premixed, and a suitable hardener is added to the crushed silt, and stirred evenly, and then granulated into balls. The premixed mixture is granulated into regular balls through equipment, and the granulated ceramsite is placed in the open air or indoor site for hardening reaction. After the reaction is completed, the ceramsite is properly post-processed, such as natural drying and screening, to meet different application requirements. The next step is to cool the sintered ceramsite. The cooling process requires strict temperature control to avoid cracks or deformation of the ceramsite due to a sudden drop in temperature. Usually, a slow cooling method is used to gradually cool the ceramsite to room temperature in the sintering furnace. The cooled ceramsite is preliminarily screened to remove unqualified products, and then surface treated. The purpose of surface treatment is to improve the physical and chemical properties of the ceramsite and enhance its performance in different applications. Common surface treatment methods include coating, impregnation and surface modification. For example, coating a layer of waterproof material on the surface of expanded clay can improve its application effect in the field of water treatment; impregnating specific chemical substances can give expanded clay the ability to adsorb harmful substances. Surface modification changes the properties of the expanded clay surface by chemical or physical methods, such as improving its hydrophilicity or hydrophobicity. The surface-treated expanded clay is then subjected to final screening and grading. According to indicators such as particle size, density, and strength, the expanded clay is divided into different grades to meet the needs of different projects and applications. For example, in the construction field, expanded clay of different strengths and densities can be used for lightweight concrete, thermal insulation materials, etc.; in the field of water treatment, expanded clay with specific particle sizes and adsorption properties can be used in sewage treatment and filtration systems. Finally, qualified expanded clay will be packaged and stored for transportation and use. In the entire preparation process, quality control is a crucial link. From raw material collection to final product, every step needs to be strictly monitored to ensure that the quality of the expanded clay meets the standards.
[0057] Working principle: first, place the motor 502 in the placement block 501, then start the motor 502 to drive the rotating column 503, the rotating column 503 passes through the through hole 506 to drive the gear 504 to rotate, the gear 504 drives the slot 508 on the outside of the adjustment column 507 to engage and connect, thereby adjusting the adjustment column 507, so as to adjust the height of the preparation body 3.
[0058] In the preparation method of molybdenum tailings ceramsite, raw materials are prepared, wherein the raw materials include molybdenum tailings, ceramic polishing waste powder, fly ash, limestone powder, cement, gypsum, alkali activator and water, wherein the 45μm sieve residue of the fly ash should be ≤20wt%, the ignition loss is 5-10wt%, the SO3 content is 0.5-3wt%, and the calcium oxide content is 1-5wt%; the 45μm sieve residue of the limestone powder should be ≤10wt%; the grade of cement is not less than 42.5; the components of the alkali activator include 15-25wt% of sodium sulfate, 30-50wt% of calcium oxide, 3-7wt% of gypsum, 15-25wt% of sodium silicate, 10 ~20wt%, in addition, the raw material components also include a grinding aid. After the prepared raw materials are processed and mixed, granulation treatment is carried out to obtain a mixture. This step may include mixing and grinding an alkali activator and gypsum in the presence of a grinding aid to obtain a prefabricated material; then the prefabricated material is mixed with molybdenum tailings, ceramic polishing waste powder, fly ash, limestone powder, cement and water to obtain a mixture; the mixture is granulated and then cured to obtain molybdenum tailings ceramsite. The granulated ceramsite needs to be cured to ensure that it has good impermeability and compression resistance, as well as good later strength. The curing conditions may include temperature, humidity and time control to ensure the quality of the ceramsite.
[0059] In the preparation process of molybdenum tailings ceramsite, the curing stage is a crucial step. The precise control of curing conditions has a decisive influence on the final performance of ceramsite. Normally, the curing temperature should be controlled between 20℃ and 80℃ to ensure that the chemical reaction inside the ceramsite can proceed smoothly, and the humidity should be maintained in the range of 60% to 90% relative humidity to prevent the surface of the ceramsite from losing water too quickly and causing cracks. The curing time is generally 24 to 72 hours, and the specific time depends on the expected performance requirements of the ceramsite. During the curing process, the chemical reaction inside the ceramsite mainly includes the reaction of the alkali activator with the active ingredients in the raw materials such as fly ash and limestone powder to generate hydration products such as hydrated calcium silicate and hydrated calcium aluminate. These hydration products It can fill the pores inside the ceramsite and improve its density and strength. At the same time, gypsum plays a role in regulating the hydration rate during the curing process to ensure that the hydration reaction inside the ceramsite is carried out evenly. After the curing is completed, the ceramsite needs to be dried to remove excess water. The drying temperature is generally controlled between 60°C and 100°C, and the drying time is about 12 to 24 hours. The dried ceramsite should be screened to remove unqualified particles and ensure that the particle size distribution of the ceramsite meets the use requirements. The final molybdenum tailings ceramsite has good physical and chemical properties and can be widely used in the construction field, such as lightweight aggregate, thermal insulation material, sound-absorbing material, etc. In addition, since its raw materials contain a large amount of industrial waste, such as molybdenum tailings and fly ash, the preparation process of the ceramsite also has the significance of environmental protection and resource recycling.
[0060] In the preparation process of ceramsite, the raw materials are first crushed and screened, and then made into raw materials of different particle sizes by rolling, balling and other methods, followed by drying and preheating. The temperature of the raw materials is controlled between 400℃ and 600℃ in the preheating stage. In the preheating stage, the organic matter and carbonate in the raw materials begin to decompose and volatilize to produce gas, and then sintering is carried out to solid-solution bond the prepared green particles at high temperature without expansion. The sintering method mainly adopts sintering by a sintering machine, which is suitable for sintering materials with stationary green particles. In the preparation of expanded clay, such as sludge expanded clay, the sludge is treated, the river sludge is deeply dehydrated, and the mud cake is crushed to ensure that the sludge is suitable for subsequent processes. Then the hardener is premixed, and a suitable hardener is added to the crushed sludge, stirred evenly, and then granulated into balls. The premixed mixture is granulated into regular balls through equipment, and the granulated expanded clay is placed in an open air or indoor site for hardening reaction. After the reaction is completed, the expanded clay is properly post-processed, such as natural drying and screening, to meet different application requirements.
[0061] In the preparation process of ceramsite, after the preparation of raw materials is completed, the next step is to cool the sintered ceramsite. The cooling process requires strict temperature control to avoid cracks or deformation of the ceramsite due to a sudden drop in temperature. Usually, a slow cooling method is adopted to gradually cool the ceramsite to room temperature in the sintering furnace. The cooled ceramsite is initially screened to remove unqualified products, and then surface treated. The purpose of surface treatment is to improve the physical and chemical properties of ceramsite and enhance its performance in different applications. Common surface treatment methods include coating, impregnation and surface modification. For example, coating a layer of waterproof material on the surface of expanded clay can improve its application effect in the field of water treatment; impregnating specific chemical substances can give expanded clay the ability to adsorb harmful substances. Surface modification changes the properties of the expanded clay surface by chemical or physical methods, such as improving its hydrophilicity or hydrophobicity. The surface-treated expanded clay is then subjected to final screening and grading. According to indicators such as particle size, density, and strength, the expanded clay is divided into different grades to meet the needs of different projects and applications. For example, in the construction field, expanded clay of different strengths and densities can be used for lightweight concrete, thermal insulation materials, etc.; in the field of water treatment, expanded clay with specific particle sizes and adsorption properties can be used in sewage treatment and filtration systems. Finally, qualified expanded clay will be packaged and stored for transportation and use. In the entire preparation process, quality control is a crucial link. From raw material collection to final product, every step needs to be strictly monitored to ensure that the quality of the expanded clay meets the standards.
[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A molybdenum ore tailings ceramsite preparation device, comprising a support block (1), characterized in that: The upper surface of the support block (1) is fixedly connected to a fixing rod (2), a side surface of the fixing rod (2) is fixedly connected to a preparation body (3), the lower surface of the preparation body (3) is fixedly connected to a connecting block (4), and the lower surface of the connecting block (4) is provided with an adjustment mechanism (5); The adjustment mechanism (5) comprises a placement block (501), a motor (502), a rotating column (503), a gear (504), a fixed block (505), a through hole (506), an adjustment column (507) and a slot (508); the placement block (501) is placed on one side surface of the support block (1); the motor (502) is mounted on the inner side surface of the placement block (501); the rotating column (503) is fixedly connected to one side surface of the motor (502); the gear (504) is fixedly connected to one side surface of the rotating column (503); the fixing block (505) is placed on one side surface of the placement block (501); a through hole (506) is provided on one side surface of the fixing block (505); the adjustment column (507) is mounted on the inner side surface of the through hole (506); and the slot (508) is provided on the outer side surface of the adjustment column (507).
2. A desulfurization and denitrification activated carbon wear resistance testing device according to claim 1, characterized in that: The fixing rod (2) is installed symmetrically with respect to the length center axis of the supporting block (1), and the connecting block (4) is installed symmetrically with respect to the width center axis of the preparation body (3).
3. A desulfurization and denitrification activated carbon wear resistance testing device according to claim 1, characterized in that: The outer surface size of the motor (502) matches the inner surface size of the placement block (501), and the motor (502) forms a threaded structure through a rotating column (503) and a gear (504).
4. A desulfurization and denitrification activated carbon wear resistance testing device according to claim 1, characterized in that: The outer surface size of the rotating column (503) matches the inner surface size of the through hole (506), and the outer surface size of the adjusting column (507) matches the inner surface size of the fixing block (505).
5. The desulfurization and denitrification activated carbon wear resistance testing device according to claim 1, characterized in that: The slots (508) are formed at equal intervals on the outer surface of the adjustment column (507), and the gear (504) is meshedly connected with the slots (508).
6. The desulfurization and denitrification activated carbon wear resistance testing device according to claim 1, characterized in that: The placement block (501) is installed symmetrically with respect to the length center axis of the support block (1), and the fixing block (505) is installed symmetrically with respect to the length center axis of the support block (1).
7. A method for preparing molybdenum ore tailings ceramsite, characterized by the following steps: The preparation method of molybdenum tailings ceramsite mainly includes the following steps: S1. Raw material preparation; S2, mixing and granulation; S3. Maintenance.
8. A method for preparing molybdenum ore tailings ceramsite, characterized by the following steps: Preparation process of ceramsite: S1. Preparation of raw materials; S2, drying and preheating; S3, sintering; S4. Special treatment.
9. A method for preparing molybdenum ore tailings ceramsite according to claim 8, characterized in that: The special treatment in S4 includes sludge treatment, hardener premixing, granulation, hardening reaction and curing treatment.